A fear-inducing odor alters PER2 and c-Fos expression in brain regions involved in fear memory. - Harry Pantazopoulos; Hamid Dolatshad; Fred C Davis (PLoS ONE, 2011)
Evidence demonstrates that rodents learn to associate a foot shock with time of day, indicating the formation of a fear related time-stamp memory, even in the absence of a functioning SCN. In addition, mice acquire and retain fear memory better during the early day compared to the early night. This type of memory may be regulated by circadian pacemakers outside of the SCN. As a first step in testing the hypothesis that clock genes are involved in the formation of a time-stamp fear memory, we exposed one group of mice to fox feces derived odor (TMT) at ZT 0 and one group at ZT 12 for 4 successive days. A separate group with no exposure to TMT was also included as a control. Animals were sacrificed one day after the last exposure to TMT, and PER2 and c-Fos protein were quantified in the SCN, amygdala, hippocampus, and piriform cortex. Exposure to TMT had a strong effect at ZT 0, decreasing PER2 expression at this time point in most regions except the SCN, and reversing the normal rhythm of PER2 expression in the amygdala and piriform cortex. These changes were accompanied by increased c-Fos expression at ZT0. In contrast, exposure to TMT at ZT 12 abolished the rhythm of PER2 expression in the amygdala. In addition, increased c-Fos expression at ZT 12 was only detected in the central nucleus of the amygdala in the TMT12 group. TMT exposure at either time point did not affect PER2 or c-Fos in the SCN, indicating that under a light-dark cycle, the SCN rhythm is stable in the presence of repeated exposure to a fear-inducing stimulus. Taken together, these results indicate that entrainment to a fear-inducing stimulus leads to changes in PER2 and c-Fos expression that are detected 24 hours following the last exposure to TMT, indicating entrainment of endogenous oscillators in these regions. The observed effects on PER2 expression and c-Fos were stronger during the early day than during the early night, possibly to prepare appropriate systems at ZT 0 to respond to a fear-inducing stimulus.